If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y(-3 + y) = -3 (-3 * y + y * y) = -3 (-3y + y2) = -3 Solving -3y + y2 = -3 Solving for variable 'y'. Reorder the terms: 3 + -3y + y2 = -3 + 3 Combine like terms: -3 + 3 = 0 3 + -3y + y2 = 0 Begin completing the square. Move the constant term to the right: Add '-3' to each side of the equation. 3 + -3y + -3 + y2 = 0 + -3 Reorder the terms: 3 + -3 + -3y + y2 = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -3y + y2 = 0 + -3 -3y + y2 = 0 + -3 Combine like terms: 0 + -3 = -3 -3y + y2 = -3 The y term is -3y. Take half its coefficient (-1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. -3y + 2.25 + y2 = -3 + 2.25 Reorder the terms: 2.25 + -3y + y2 = -3 + 2.25 Combine like terms: -3 + 2.25 = -0.75 2.25 + -3y + y2 = -0.75 Factor a perfect square on the left side: (y + -1.5)(y + -1.5) = -0.75 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 3x+5y=42 | | -9=9(9+5t) | | 3(2y+3)= | | 0.545454545455*10000= | | 8ln(4x)=56 | | 215=5(3-5m) | | y=430x+1000 | | 6x^2-7x+8=x+5 | | .06x+x=159 | | y-3x=19slope | | 3+m=(-6) | | -4(n+2)=-2(2n-1) | | -(4-x)=.75(x-6) | | a(20)+319-a(10)=5860 | | 4x-5+3x+5=40 | | -7x-35=-7x-35 | | -4(6-5x)=96 | | 3s+9(8+2s)= | | 4(7+y)=16-3y | | 2c-c-c+3c=15 | | (100+40y+3y^2)(100+40y+3y^2)=0 | | 4+5(1+f)= | | 4x+9=x-18 | | 6t+2(4t+5)= | | 405=80n-25 | | 4.5-2k=6 | | 5+9(2+7j)= | | 6b+19=25 | | .5(16-x)=-12(x+7) | | 4x-7=4(x+5) | | X-8-1=3+4k+k | | -2x=2-(-10) |